61.6.1 problem 18

Internal problem ID [12142]
Book : Handbook of exact solutions for ordinary differential equations. By Polyanin and Zaitsev. Second edition
Section : Chapter 1, section 1.2. Riccati Equation. subsection 1.2.4-2. Equations with hyperbolic tangent and cotangent.
Problem number : 18
Date solved : Tuesday, January 28, 2025 at 12:34:09 AM
CAS classification : [_Riccati]

\begin{align*} y^{\prime }&=y^{2}+a \lambda -a \left (a +\lambda \right ) \tanh \left (\lambda x \right )^{2} \end{align*}

Solution by Maple

Time used: 0.004 (sec). Leaf size: 122

dsolve(diff(y(x),x)=y(x)^2+a*lambda-a*(a+lambda)*tanh(lambda*x)^2,y(x), singsol=all)
 
\[ y = \frac {\operatorname {LegendreP}\left (\frac {a +\lambda }{\lambda }, \frac {a}{\lambda }, \tanh \left (\lambda x \right )\right ) \lambda +\operatorname {LegendreQ}\left (\frac {a +\lambda }{\lambda }, \frac {a}{\lambda }, \tanh \left (\lambda x \right )\right ) c_{1} \lambda -\tanh \left (\lambda x \right ) \left (c_{1} \operatorname {LegendreQ}\left (\frac {a}{\lambda }, \frac {a}{\lambda }, \tanh \left (\lambda x \right )\right )+\operatorname {LegendreP}\left (\frac {a}{\lambda }, \frac {a}{\lambda }, \tanh \left (\lambda x \right )\right )\right ) \left (a +\lambda \right )}{c_{1} \operatorname {LegendreQ}\left (\frac {a}{\lambda }, \frac {a}{\lambda }, \tanh \left (\lambda x \right )\right )+\operatorname {LegendreP}\left (\frac {a}{\lambda }, \frac {a}{\lambda }, \tanh \left (\lambda x \right )\right )} \]

Solution by Mathematica

Time used: 5.214 (sec). Leaf size: 325

DSolve[D[y[x],x]==y[x]^2+a*\[Lambda]-a*(a+\[Lambda])*Tanh[\[Lambda]*x]^2,y[x],x,IncludeSingularSolutions -> True]
 
\begin{align*} y(x)\to \frac {a \int -\frac {\lambda \left (2-2 e^{-2 \lambda x}\right )}{e^{2 \lambda x}+1} \, de^{2 \lambda x}}{2 \lambda }+\frac {-2 \lambda \exp \left (\int _1^{e^{2 x \lambda }}\frac {\frac {a (K[1]-1)}{\lambda (K[1]+1)}-1}{K[1]}dK[1]+2 \lambda x\right )-2 \lambda \exp \left (\int _1^{e^{2 x \lambda }}\frac {\frac {a (K[1]-1)}{\lambda (K[1]+1)}-1}{K[1]}dK[1]+4 \lambda x\right )+a \left (e^{2 \lambda x}-1\right ) \int _1^{e^{2 x \lambda }}\exp \left (\int _1^{K[2]}\frac {\frac {a (K[1]-1)}{\lambda (K[1]+1)}-1}{K[1]}dK[1]\right )dK[2]+a c_1 e^{2 \lambda x}-a c_1}{\left (e^{2 \lambda x}+1\right ) \left (\int _1^{e^{2 x \lambda }}\exp \left (\int _1^{K[2]}\frac {\frac {a (K[1]-1)}{\lambda (K[1]+1)}-1}{K[1]}dK[1]\right )dK[2]+c_1\right )} \\ y(x)\to \frac {a \left (e^{2 \lambda x}-1\right )}{e^{2 \lambda x}+1}+\frac {a \int -\frac {\lambda \left (2-2 e^{-2 \lambda x}\right )}{e^{2 \lambda x}+1} \, de^{2 \lambda x}}{2 \lambda } \\ \end{align*}